ANALISIS PENGELOLAAN AMENITAS DI DESA WISATA KETAPANRAME BERBASIS PLANNING: Studi Kasus pada Desa Wisata Ketapanrame, Kecamatan Trawas, Kabupaten Mojokerto - Princes Arsaredima Fahlevi; Garsione Agni Andrea (Journal Publicuho, 2025)
This study aims to analyse the planning function in the management of amenities at Ketapanrame Tourism Village, Trawas District, Mojokerto Regency. The research employed a descriptive qualitative approach, with data collected through in-depth interviews, participatory observation, and document analysis. The findings reveal that the planning function has been implemented in a structured and participatory manner through five key indicators: goal setting, program formulation, budgeting, activity scheduling, and development planning. Goals are set clearly and measurably in line with the village vision; programs are formulated collaboratively involving multiple stakeholders; budgeting focuses on facilities with direct benefits to visitors through a phased development strategy; activity scheduling is adaptively arranged according to tourist seasons; and development planning considers environmental sustainability and village spatial layout. Although limited funding remains a challenge, the phased development strategy and multi-stakeholder involvement serve as adaptive measures that support the sustainable management of amenities in the tourism village.